Optimization of electrical submersible pump artificial lift system for extraheavy oils through an analysis of bottom dilution scheme - Díaz-Prada, Carlos Andrés; Guarín Arenas, Flaminio; González-Barbosa, Javier Enrique; García Chinchilla, César Augusto; Cotes León, Esperanza de Jesús; Rodríguez Walteros, Carolina (CT&F - Ciencia, Tecnología y Futuro, 2010)
This study presents the analysis of the variables that have the greatest impact on energy requirements for an artificial lift system applied to extra heavy crude oils, considering an uncertainty behavior analysis through their sensitivity in the vertical flow modeling implemented for a Chichimene Field well. The selected variables are the viscosity and fluid density, the required artificial lift system pressure differential, well depth, the flow rate of produced fluids and the dilution percentage. The oil produced in this field has a density of 7,8 °API, and the well studied features a water cut of about 10% and produces a total of 2400 BOD. For this flow naphtha dilution rates were defined using up to 20% by volume. The ranges of energy required for the lifting system for different scenarios raised by the analysis variables were also determined. For these conditions a variation of the energy required 20% for a fluid flow incremental of 50 BFOD was obtained, as established from the flow capacity of the well and the pressure required for sustaining a pressure head of 100 psi and 400 psi. Bottom dilution scheme establishes a change in artificial lift system energy requirement, of up to 25% for a 15% of diluter, whereas the relationship between the volumes produced and the system arrays gives an energy efficiency of 40%.